Photoconductivity mechanism in structures with Ge-nanoclusters grown on Si(100) surface - Melnichuk, Ye.Ye.; Hyrka, Yu.V.; Kondratenko, S.V.; Kozyrev, Yu.N.; Lysenko, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Interband optical transitions in the epitaxial Si/Ge heterostructures with Ge nanoislands grown on Si(100) surface were investigated using photocurrent spectroscopy. The mechanism of photoconductivity was discussed. It was shown that electron transitions from the ground state of the valence band in a quantum dot to the conduction band of Si surrounding make the main contribution into monopolar photoconductivity below the fundamental absorption edge of crystalline Si. Photoexcited holes were found to be localized in Ge nanoislands inducing the lateral conductivity changes in the near-surface depletion layer of p-Si substrate due to the field-effect.